Towards a Taoist aesthetics of data visualization. - Li, Qi (Digital Scholarship in the Humanities, 2020)
As a dominant Western aesthetics, the Kantian sublime involves power over nature perceived from a distance. In the Kantian model, the sublime oscillates between the mathematical sublime—emphasizing the vastness of nature that exceeds the comprehension of the viewer—and the dynamic sublime, in which the viewer attempts to establish a sense of control over nature. In big data visualization based on the sublime, users tend to apprehend the magnitude of data from a distance, provoking an experience of fear or awe over the immense scale of technology. Such a model is predicated on a dualism between body and data. In contrast to Kantian dualism, Taoist philosophy privileges the integration of data, body, and nature. This article theorizes the Taoist body in relation to digital technology by, firstly, critiquing the Kantian sublime that underpins much data visualization. Visualization based on Taoist embodiment leads to a more harmonious integration of human experience and data, promoting emotional, psychological, and health-related dimensions. Towards a model of Taoist embodiment of big data, interactive digital technology is key. This article concludes with examples of data-based, participatory, and installation art, including my interactive work Taiji (2013–15) centred on the embodied visualization of electroencephalography data.